2015
DOI: 10.1007/s10803-015-2481-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Parent- and Child-Rated Anxiety Measures in Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) and anxiety frequently co-occur. Research on the phenomenology and treatment of anxiety in ASD is expanding, but is hampered by the lack of instruments validated for this population. This study evaluated the self- and parent-reported Revised Child Anxiety and Depression Scale and the Multidimensional Anxiety Scale in Children-2 among 46 youth with ASD. Internal consistency and test-retest reliability were acceptable, but inter-rater reliability was poor. Parent-child agreement wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 57 publications
2
37
0
Order By: Relevance
“…Although there are numerous studies in which high functioning individuals with ASD have reported affective states using self-report instruments (e.g., Sasson et al, 2012; Tseng et al, 2014; White et al, 2014), another potential limitation of the present study is the long-standing issue of the validity of self-report of affective states in ASD (Berthoz & Hill, 2005; Kaat & Lecavalier, 2015), and future research that addresses the correspondence between self- and caregiver-report indices of positive affect in ASD will be needed to address this issue. We highlight in this regard, however, that the ASD and control groups in this study showed relatively equivalent levels of positive affect, suggesting that the ASD group understood the meaning of PANAS-C items (although this observation is clearly not sufficient to establish the validity of self-reported positive affect in the ASD group, which should be addressed in future studies).…”
Section: Discussionmentioning
confidence: 90%
“…Although there are numerous studies in which high functioning individuals with ASD have reported affective states using self-report instruments (e.g., Sasson et al, 2012; Tseng et al, 2014; White et al, 2014), another potential limitation of the present study is the long-standing issue of the validity of self-report of affective states in ASD (Berthoz & Hill, 2005; Kaat & Lecavalier, 2015), and future research that addresses the correspondence between self- and caregiver-report indices of positive affect in ASD will be needed to address this issue. We highlight in this regard, however, that the ASD and control groups in this study showed relatively equivalent levels of positive affect, suggesting that the ASD group understood the meaning of PANAS-C items (although this observation is clearly not sufficient to establish the validity of self-reported positive affect in the ASD group, which should be addressed in future studies).…”
Section: Discussionmentioning
confidence: 90%
“…This often necessitates obtaining multi‐informant reports from caregivers or significant others. Although agreement in anxiety ratings between caregivers and children with ASD has ranged from poor [i.e., Kaat & Lecavalier, ; Kerns et al, ; Renno & Wood, ] to moderately good [i.e., Blakeley‐Smith, Reaven, Ridge, & Hepburn, ; Magiati, Chan, Tan, & Poon, ; Ozsivadjian, Hibberd, & Hollocks, ; van Steensel et al, ], storch et al [] found that parental reports contributed significantly to the clinical diagnosis of anxiety. Thus, parent report remains an important way of assessing anxiety in youth with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Second, several symptoms of anxiety, such as social withdrawal and insistence upon sameness, are also symptoms of autism, making it difficult to differentiate which underlying disorder is the cause of outward behaviors (Baron, 2006; Kuusikko et al, 2008; White et al, 2009; Kerns & Kendall, 2012; Hallet et al, 2013; van Steensel, Bogels, & Wood, 2013; White et al, 2014). Third, there is limited agreement between parent- and child-reported scores on anxiety surveys in this population (Kaat & Lecavalier, 2015). The combination of these factors has fostered a general distrust of commonly used anxiety measures in ASD.…”
mentioning
confidence: 99%
“…By using several standardized anxiety measures, a combination of self- and parent-reports, and biophysiological responses to task-evoked stress, we aimed to improve our understanding of how adolescents with ASD experience and express anxiety during social context. We predicted that parent- and self- reports in the ASD cohort will reflect higher levels of trait anxiety than in the TD group (Kaat & Lecavalier, 2015). We also anticipated that adolescents with ASD would show more pronounced changes in sympathetic and parasympathetic activity (state anxiety) during a high-stress task than their TD peers, and that these changes would correspond to higher levels of trait anxiety in this population.…”
mentioning
confidence: 99%